Road landscape and engineering system Kyiv-Odesa: functioning, current geochemical state, problems of rational use - Denysyk, Hrigoriy; Ataman, Liudmyla; Denysyk, Bogdan (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Formulation of the problem. The Kyiv-Odesa road landscape engineering system, one of the most powerful within Ukraine, is an optimal model for detailed studies of such status. Research into the unique history of the formation of the Kyiv-Odesa DLF, its modern structure and properties, the manifestation of adverse processes, and the development of measures to optimize them has significant scientific and practical significance, and will also be an incentive for conducting similar studies of other DLFs of Ukraine. The goal is to study the features of formation, functioning and current geochemical state of road and adjacent landscapes for their further rational use using the example of the most powerful landscape and engineering system Kyiv-Odesa in Ukraine. Methods. In the process of research, landscape: dynamic, geochemical and ecological approaches and their corresponding methods: field landscape research, analysis and synthesis, historical and geographical, cartographic and modelling were applied. GIS technology methods were used as cross-cutting ones. Main Results. It is noted that road landscapes, especially their more widespread and dynamic landscape and engineering systems, are paid little attention by geographers and landscape scientists of Ukraine. It is shown that in the structure of modern road landscapes of Ukraine it is advisable to distinguish three of their components (subsystems): road landscape-engineering systems and road landscape-technogenic, which are often combined under the general name road landscape-engineering systems and non-functioning road landscapes – non-operating road systems that are not supported by man and develop according to natural laws. During 2018-2021, geochemical studies were conducted on the content of heavy metals (zinc, lead, cadmium and copper) in soil and snow cover, their migration and accumulation in roadside strips of the actively operating Kyiv-Odesa road landscape-engineering system. It was established that here heavy metals actively accumulate in soil and snow cover, only cadmium accumulates, which is self-purified in the soil. In some natural areas of the Kyiv-Odesa DLF, anomalous areas were identified, where the zinc and lead content exceeded the MPC norm by 2-3 times. 4 zones of heavy metal pollution were identified: intensive pollution (0-5 m from the roadway); medium pollution (5-10 m); weak pollution (10-15 m) and relatively clean (more than 20 m from the highway). Conclusions. In general, despite its capacity, the Kyiv-Odesa road landscape and engineering system is not critically polluted with heavy metals, which indicates its ability to self-clean. It is noted that in the future, more attention should be paid not only to geochemical and ecological, but also to their geophysical, recreational, and aesthetic problems of the functioning of road landscapes.